2021
DOI: 10.14507/epaa.29.6351
|View full text |Cite
|
Sign up to set email alerts
|

Digital divides: K-12 student profiles and online learning

Abstract: Online learning for primary and secondary students has expanded significantly in the United States during the last two decades. In addition to the sustained growth of online learning, many schools and districts used online learning to respond to the coronavirus pandemic. As school leaders and policymakers move more students into online courses, they need information about which students succeed and struggle online. We examine the relationship between student traits and academic success in a statewide online le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
5
0
2
Order By: Relevance
“…Compared to traditional face‐to‐face classroom learning environments, online learning environments lack of a framework encouraging students to learn, a learning atmosphere, as well as the opportunities for student interaction and collaboration, which can results in lower learning engagement (Bouhnik & Marcus, 2006; Tuckman, 2007). In particular, K‐12 students often exhibit low engagement in learning poor academic performance in online learning environment because of their lack of online learning experience and inability to adapt to the rapid transition from a classroom environment to online learning environments (Chiu, 2021a; Mann et al, 2021). Moreover, many studies have shown that most teachers have no experience of online teaching online and teaching strategies on how to improve student engagement in online learning (An et al, 2021; Chiu, 2017; Huh & Reigeluth, 2017; Moore‐Adams et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to traditional face‐to‐face classroom learning environments, online learning environments lack of a framework encouraging students to learn, a learning atmosphere, as well as the opportunities for student interaction and collaboration, which can results in lower learning engagement (Bouhnik & Marcus, 2006; Tuckman, 2007). In particular, K‐12 students often exhibit low engagement in learning poor academic performance in online learning environment because of their lack of online learning experience and inability to adapt to the rapid transition from a classroom environment to online learning environments (Chiu, 2021a; Mann et al, 2021). Moreover, many studies have shown that most teachers have no experience of online teaching online and teaching strategies on how to improve student engagement in online learning (An et al, 2021; Chiu, 2017; Huh & Reigeluth, 2017; Moore‐Adams et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Prior to 2022, the top challenges of online learning for K-12 learners include inequity of technology and materials, lack of online teaching knowledge (Vinson & Caukin, 2021 ), unstable internet connection, and unfamiliar with the learning platforms and software (Zuo et al, 2021 ), among many others. Yet looking into the post-pandemic time, many schools and districts used online learning to respond to the pandemic and continue to use e-learning technologies to assist students to achieve learning success (Mann et al, 2021 ). Owens and Hite's ( 2022 ) study reported implementing a STEM learning experience using a virtual global collaboration project-based learning approach using Canvas as the learning platform and achieved satisfying learning results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior to 2022, the top challenges of online learning for K-12 learners include inequity of technology and materials, lack of online teaching knowledge (Vinson & Caukin, 2021 ), unstable internet connection, and unfamiliar with the learning platforms and software (Zuo et al, 2021 ), among many others. Looking into the post-pandemic era, many schools and districts continue to use e-learning technologies to assist students to achieve learning success (Mann et al, 2021 ). On the other hand, the emergence of PBL e-learning platforms posts challenges for educators to choose the right platform for the targeted learners.…”
Section: Introductionmentioning
confidence: 99%
“…While the growth of online education has been well-documented, there is less research on the impact of online learning on minority students, particularly African American students. Previous studies have found that African American students often face additional challenges when enrolled in online courses due to the digital divide [6,7]. These challenges include inadequate access to technology, lack of access to high-speed internet, and lack of familiarity with online learning environments [8,9].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The impact of race and financial background on student success in online learning has also been explored in previous research. Studies have found that students from lower-income backgrounds and minority students face greater challenges in online learning, such as limited access to technology and the internet [7,11,15].…”
Section: Literature Reviewmentioning
confidence: 99%